INFLUENCE OF TURBIDITY ON THE SHOALING PREFERENCES OF PUNTIUS SARANA SUBNASUTUS - N., JILNA ALEX; K., JOHN THOMAS (Journal of the Inland Fisheries Society of India, 2021)
Turbidity is one of the important physical characteristic of water that affects its optical property. At extremely high levels, turbidity can directly affect fish growth and survival, for example, by interfering with gill function or the quality of substrata for egg laying (Bash et. al., 2001). By limiting the photic zone, turbidity can also reduce the foraging success by diminishing the prey contrast (Sweka and Hartman, 2001) or it may reduce the time available for the prey to detect predators (Berger et al., 2004).